Menyoal Agama Para Nabi dan Rasul Terdahulu Antara Agama Islam dan Agama Tauhid (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Islam consists of faith and Sharia, so that Din there’s have faith and Sharia (Islamic), that is Islam, but if only faith just the same as the teachings of the Prophets before, so that the teaching them insufficient to refered the Islamic Shariah (Islam). Islam is a religion (ad-dîn) has been revealed by Allah swt. to Prophet Muhammad saw. To organize the relationship of man with Allah, by himself and with his fellow. To Religious expression (ad-dîn) has been revealed by Allah swt., all could be accept it, like same is the case with human contact to arrange with Allah, with himself and with his fellow, we have been happy and could be accept it, because it's described the scope of Islam completely. But Religious expression (ad-dîn) has been revealed by Allah swt. to Prophet Muhammad saw., which means that Islam is a religion that was revealed to Prophet Muhammad saw. alone, and not the religion that has been revealed to the Prophets before, perhaps this is what the expressions indeed require an explanation. For to that this article was given to explain it.